Assessment of the nanotechnology R&D programs funded by the Department of Science and Technology (DOST) - Reyes, Meraida D. (University of the Philippines Diliman, 2014)
Nanotechnology can be defined as 'engineering at a very small scale', and this term can be applied to many areas of research and development - from medicine to manufacturing to computing, and even to textiles and cosmetics. Nanotechnology initiatives in other countries started nearly a decade ago. The Philippines through the Department of Science and Technology (DOST) launched the Nanotechnology R&D Roadmap of the Philippines in year 2009. After five years of implementation, it is the objective of this study to : (a) assess the various nanotechnology R&D programs and/or projects funded or currently being funded by DOST; (b) determine if the Philippines is developing its own niche in nanotechnology; (c) assess qualitatively the Nanotechnology R&D programs using four principles of assessing performance, namely, alignment, linkages, excellence and enabling environment. Results of the study showed that the level and quality of inputs that are provided to Nanotechnology R&D are variable. R&D spending infrastructure investments in recent years have continued to grow and are still expected to rise until 2016. There is no formula which can be applied to dictate the optimum allocation of funds between programs. The use of the R&D performance evaluation techniques as explained under the given conceptual framework will provide the government a fund-allocation basis in the future. In the years to come, performance assessment of nanotechnology R&D and other major programs of DOST could be enhanced based on the several recommendations provided in this paper.